Perkawinan Islam Wetu Telu Masyarakat Bayan Lombok Utara - Arnis Rachmadhani (Analisa: Journal of Social Science and Religion, 2011)
This article examines the doctrine of marriage in Wetu Telu society inBayan, North Lombok. According to the community marriage is carried outby three steps: perondongan, mepadik lamar, and selarian which is finishedwith some rituals, such as menjojok, memulang, sejati, pemuput selabar,akad nikah, sorong serah, nyongkolan, and balik onos nae. The marriageritual is led in accordance with Islamic teachings by the Head of Office ofReligious Affairs. In spite of referring to Islamic sharia, the Wetu Telu also strongly holdsthe teaching of their ancestors which is more identical with Siva-Buddhistteaching. After a long process of acculturation with Hinduism, the latertakes a part in marriage process within the Wetu Telu. Therefore, the mar-riage concept carried out by the Wetu Telu is a combination of Siva-Budhist (as the religion of indigenous people) and Balinese Hinduism carried out byBalinese kingdom which had been mixed with Islamic teachings that laterbecome local tradition. This local tradition then does create social stratification, marriage procedures and marriage procession. The local wisdom of marriage among the Wetu Telu has a potential role to strengthen religiousharmony in multicultural society.